Best Answer

Each number is -4 times the previous one. That means that you can write a recursive rule as:

f(1) = -3

f(n) = -4 * f(n-1)

The explicit rule involves powers of -4; you can write it as:

f(n) = -3 * (-4)^(n-1)

Q: What is the recursive rule and explicit rule for -3 12 -48 192?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

Each number is -4 times the previous one. That means that you can write a recursive rule as: f(1) = -3 f(n) = -4 * f(n-1) The explicit rule involves powers of -4; you can write it as: f(n) = -3 * (-4)^(n-1)

-7

The LCM is 192.

12

There are 12 inches in one foot. therefore, 192 inches is equal to 192 / 12 = 16 feet.16 ft.

12 in × 16 in = 192 sq in

1.6 x 12 = 19.2

192 ounces * 1 pound/16 ounces = 12 pounds

The GCF of 192 and 252 is 12.

The GCF of 180, 192 is 12.

192 = 16 x 12

12